In vitro responses of water lily Nymphaea lotus to the growth regulators kinetin and indole-3-butyric acid - Sulaiman, E.; Rashid, A. A.; Aziz, M. A.; Kamarudin, M. S. (Malaysian Society of Plant Physiology, 2001)
A protocol for in vitro shoot production was investigated using axillary buds obtained from tubers of Nymphaea lotus. Effects of kinetin (0, 1.0, 2.5. 5.0 and 10 mg/L) and IBA (0. 0.5 and 1.0 mg/L) were examined. Kinetin at 2.5 mg/L either alone or in combination with 1.0 mg/L IBA and kinetin at 5.0 mg/L in combination with 0.5 mg/L IBA resulted in a high proliferation of shoots. Increasing the kinetin concentration to 10 mg/L, at all levels of IBA. reduced the number of shoots produced and the shoots were apparently stunted.